Tata Kelola Kolaboratif dalam Penanggulangan Genangan Air di Jalan Temanggung Tilung Kota Palangka Raya - Muhammad Aji Fahreji; Mutia Zakia Rahma; Lie Aditya Pratama; Aina Jannah; Leviano Rafly; Marvy Ferdian Agusta Sahay (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Waterlogging in Jalan Temanggung Tilung, Palangka Raya City, frequently occurs during periods of high rainfall and affects community activities. This study aims to analyze collaborative governance in addressing water inundation and to identify the roles of the stakeholders involved. The research employed a qualitative descriptive approach using interviews, observation, and documentation as data collection techniques. The findings indicate that water inundation is influenced by topographical conditions, urban development, and limited drainage capacity. Collaborative governance has been implemented through inter-agency coordination, clear role distribution, and community participation in development planning forums. However, several challenges remain, including budget limitations, low public awareness of drainage maintenance, and technical obstacles in the field. Therefore, stronger collaboration among stakeholders is needed to improve the effectiveness of water inundation management in Palangka Raya City.